Modelling of periodic heterostructures based on tin and phosphorus chalcogenides - Klevets, V.Yu.; Savchenko, N.D.; Shchurova, T.N.; Opachko, I.I.; Popovic, K.O. (Functional Materials, 2013)
In terms of tight-binding approximation and pseudopotential theory the following energy parameters for binary tin and phosphorus chalcogenides: band gap, electron affinity energy and energy position of Fermi level have been calculated. The effect of spin-orbit interaction, chemical bond polarity, d-states, and the intra-atomic Coulomb repulsion energy on the energy band parameters has been analyzed. Energy band diagrams for binary tin and phosphorus chalcogenides, as well as for periodic SnSe–PSe heterostructures dependent on the way of Fermi level determination have been given.